Analyses of motion and drag coefficient of water droplets in a natural draught cooling tower - Liu, Baomin; Hawlader, Mohammad Nurul Alam (IIUM Press, 2011)
Cooling towers have been widely used in power plants and space air conditioning systems. The rain region plays an important role in the operation of cooling towers. In this paper, four different models have been investigated that describe the motion of water droplets in the rain region of a cooling tower. Due to the non-uniformity of the flow, heat and mass transfer processes inside the cooling tower, the velocity field of water droplets is, at least, two-dimensional. Therefore, these models were tested with a numerical simulation program that accounts for the non-uniform now. The velocity fields of water droplets, the variations of the drag coefficient with the relative velocity of water droplets have been predicted. The effect of drag and buoyancy force on the motion of water droplets were also studied numerically. The model based on Dreyer and Erens's correlation has been found to represent the actual situation reasonably well and is recommended for the modelling of water droplets motion in cooling towers.